Performance determinants in an individual ski mountaineering race: A literature review - Løkken, S.; Røst, J.; Olsen, S. B. (Norwegian University of Science and Technology, 2022)
Purpose: The purpose with this review was to investigate which determinants that are important for performance in an individual ski mountaineering race. Methods: A literature search was carried out in the databases PubMed and SPORTdiscus on keywords related to performance, physiology and ski mountaineering. The search resulted in seven studies. All studies had to investigate how different factors affected race performance. Results: VO2max (r = 0.71-0.87), VO2 @ VT1 (r = 0.607-0.90) and VO2 @ VT2 (r = 0.694-0.91) and body fat percentage (r = 0.72-0.782) correlated with race performance. Conclusion: VO2max, VO2 @ VT1, VO2 @ VT2 and body fat percentage were all important determinants for race performance in an individual ski mountaineering race.